2011
DOI: 10.1016/j.ijrobp.2010.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Study of Neoadjuvant Bevacizumab and Radiotherapy for Resectable Soft Tissue Sarcomas

Abstract: Purpose Numerous preclinical studies demonstrate that angiogenesis inhibitors can increase the efficacy of radiation therapy (RT). We sought to examine safety and efficacy of bevacizumab (BV) and RT in soft tissue sarcomas (STS) and explore biomarkers for treatment response. Methods and Materials Patients (pts) with ≥5 cm, intermediate- or high-grade STS at significant risk of local recurrence (LR) received neoadjuvant BV alone followed by BV plus RT prior to surgical resection. Correlative science studies i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 24 publications
4
54
0
Order By: Relevance
“…Consistent with multiple prior studies of anti-VEGF/VEGFR agents, including bevacizumab in sarcoma, rectal, breast, and ovarian cancer, we found that anti-VEGF therapy led to a sustained increase in PlGF, suggesting that this may be a pharmacodynamic marker of activity (21)(22)(23)(24)(25)(26)(27)(28). We also found that, although pretreatment plasma VEGF does not associate with outcome, higher levels of sVEGFR1 before combination therapy were associated with worse survival.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with multiple prior studies of anti-VEGF/VEGFR agents, including bevacizumab in sarcoma, rectal, breast, and ovarian cancer, we found that anti-VEGF therapy led to a sustained increase in PlGF, suggesting that this may be a pharmacodynamic marker of activity (21)(22)(23)(24)(25)(26)(27)(28). We also found that, although pretreatment plasma VEGF does not associate with outcome, higher levels of sVEGFR1 before combination therapy were associated with worse survival.…”
Section: Discussionsupporting
confidence: 89%
“…A small study of neoadjuvant bevacizumab and RT in patients with STS (30% of which were retroperitoneal) suggested bevacizumab might increase the sensitivity of such tumors to radiation without significant adverse events. 50 On multivariate analysis, this series of patients also suggested that age above 65 years and male sex were associated with a worse prognosis regarding high-grade RPS after surgical resection. These are both in agreement with current literature.…”
Section: Discussionmentioning
confidence: 65%
“…Nevertheless, the targeted agents sorafenib [16], bevacizumab [17], and pazopanib exert their anti-tumor activity by targeting the tumor vasculature, and are or have been studied in combination with RT. sunitinib combined with RT is currently under investigation [18] and further discussed below.…”
Section: Discussionmentioning
confidence: 99%